1993
DOI: 10.3146/i0095-3679-20-1-7
|View full text |Cite
|
Sign up to set email alerts
|

A Note On Broad-Sense Heritability of Selected Sensory Descriptors in Virginia-Type Arachis Hypogaea L.1

Abstract: Improvement of flavor quality is a breeding objective that merits increased attention. To obtain further information on broad-sense heritability of selected sensory attributes, 30 virginia-type genotypes sources were grown in replicated experiments at two locations during 1988 for evaluation. Roasted peanut paste samples were evaluated for 14 sensory attributes. Fruity attribute was confirmed as having a significant suppressive effect on roasted peanut attribute. Session-to-session variation was significant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 0 publications
0
58
0
Order By: Relevance
“…The roasted flavor of peanuts is unique and investiga tion of heritability of the roasted peanut component of this complex flavor has been conducted by Pattee and coworkers (Pattee and Giesbrecht, 1990;Pattee et al, 1993). They found that parental lines influence flavor and that the identification of peanut germplasm with high roast flavor quality will be important to improve roast peanut flavor in future cultivars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roasted flavor of peanuts is unique and investiga tion of heritability of the roasted peanut component of this complex flavor has been conducted by Pattee and coworkers (Pattee and Giesbrecht, 1990;Pattee et al, 1993). They found that parental lines influence flavor and that the identification of peanut germplasm with high roast flavor quality will be important to improve roast peanut flavor in future cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…In general, var. hirsuta peanuts con tained more free sugars (141-178 μπιοΐ/g defatted meal) and free amino acids (18.5-37.2 μπιοΐ/g defatted meal) than Florunner (127 and 20.2 μπιοΐ/g defatted meal free sugars and free amino acids, respectively) or NC 7 (122 and 20.3 μπιοΐ/g defatted meal).Key Words: Tocopherols, [oil content, oleic/linoleic acid ratio, free amino acids, «free sugars, oil stability index.The roasted flavor of peanuts is unique and investiga tion of heritability of the roasted peanut component of this complex flavor has been conducted by Pattee and coworkers (Pattee and Giesbrecht, 1990;Pattee et al, 1993). They found that parental lines influence flavor and that the identification of peanut germplasm with high roast flavor quality will be important to improve roast peanut flavor in future cultivars.…”
mentioning
confidence: 99%
“…It also was shown that there are highly significant correlations among least square means for the attributes, particularly bitter with sweet and roasted peanut with sweet and bitter (Pattee et al, 1997(Pattee et al, ,1998. Additionally, they have shown that certain roasted peanut quality sensory attributes are heritable traits (Pattee AND Giesbrecht, 1990;Pattee et al, 1993Pattee et al, , 1995Pattee et al, , 1998Isleib et al, 1995). Thus, through these efforts the long standing objective of the peanut industry to enhance the intensity of roasted peanut flavor in peanut products is being addressed.…”
mentioning
confidence: 99%
“…To some degree, the very large estimates of dominance variance may be artifacts due to the very small coefficients where CJ~was the estimate of additive genetic variance, CJ~A the estimate of nonadditive genetic variance due to dominance or epistasis, CJ~the estimate of location-by-additive interaction variance, CJ~NA the estimate of location-by-nonadditive interaction variance, CJ~the estimate of panel-to-panel variance, and o~the estimate of plot-to-plot environmental variance. (1990) and Pattee et al (1993). Two sessions were conducted each week on nonconsecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…effects of genotype, environment, and their interaction (Pattee and Giesbrecht, 1990;Pattee et al, 1993Pattee et al, , 1997; high oleic acid content (Pattee and Knauft, 1995); and roast color and fruity attribute (Pattee et al, 1991;. Isleib et al (1995Isleib et al ( ,2000 have shown that failure to monitor and evaluate these characteristics can lead to serious quality defects in new breeding lines and cultivars.…”
mentioning
confidence: 99%